Expression profile of ovarian tumors: distinct signature of Sertoli–Leydig cell tumor. Issue 6 (1st October 2006) - Baranova, A.; Gowder, S.; Naouar, S.; King, S.; Schlauch, K.; Jarrar, M.; Ding, Y.; Cook, B.; Chandhoke, V.; Christensen, A.
Abstract : Epithelial ovarian tumors are the most common subtype of ovarian cancer. In this study, we reveal distinct expression signatures of previously uncharacterized ovarian carcinoma subtypes, including endometrioid component of mixed ovarian tumor and Sertoli–Leydig tumor. Both subtypes were compared to the most common and well-characterized ovarian epithelial carcinoma of the serous type. These comparisons were performed by complementaryDNA (cDNA) microarrays allowing high-fidelity measurements of the expression levels of 39, 360 human individual cDNA species representing both known and unknown human genes. Functional analysis of differentially expressed genes in Sertoli–Leydig tumor revealed an upregulation in sonic hedgehog pathway, deregulation of several metabolic pathways especially in amino acid metabolism and overexpression of genes associated with protein synthesis, including ribosomal genes.